MgAl-Layered Double Hydroxide Nanoparticles as Smart Nanofillers To Control the Rheological Properties and the Residual Porosity of Cement-Based Materials - Almeida, Adriana A. [UNESP]; Santos, Rodrigo M. M. [UNESP]; Alves Rosa, Marinalva A. [UNESP]; Pulcinelli, Sandra H. [UNESP]; John, Vanderley M.; Santilli, Celso V. [UNESP] (American Chemical Society (ACS), 2022)
Nanotechnology in building materials has still not been widely explored, despite its great potential in developing a new generation of smart and eco-efficient cementitious materials based on the addition of nanoparticles. In this context, layered double hydroxides (LDH) are a family of anionic clays that can regenerate their nanostructure after thermal decomposition to the corresponding mixed oxides (MO). This memory effect involves the reversible recrystallization of the LDH nanoparticles from nanocrystalline MO in contact with water or anionic solutions. It has shown promise in the immobilization of different anions, such as chloride and carbonate, that could compromise the durability of reinforced concrete. This study proposes the incorporation of nanocrystalline MO in the cementitious matrix to control the rheological properties of the paste and reduce the porosity of the cement because the regeneration of the lamellar nanostructure occurs by the dissolution and reprecipitation of LDH nanoparticles inside the pores formed during the consolidation of the paste. Time-resolved wide-angle X-ray scattering (WAXS) was used to study the mechanism of regeneration of the LDH structure following contact of the MO with the cement pore solution. The results showed that the regeneration of the LDH, which occurs by an aggregative growth of anisotropic nanoparticles, changed the rheological behavior by increasing the elastic modulus (G′) and consequently contributing to the consolidation of the paste, demonstrating the potential of these materials for application in three-dimensional (3D) printing. Regarding the pore structure of the hydrated cement, a porosity reduction of up to 20% was observed with the addition of 2.0 wt % of MO. Furthermore, after 28 days of hydration, the specific surface area of the cement was reduced from 60 to 36 m2g-1with the incorporation of 1.0 wt % of MO. The use of LDH nanoparticles as a cement smart nanofiller proved to be advantageous in the kinetic control of cement curing and improvement of the porous structure of the hydrated cement.
Keywords: cement; intercalation; lamellar nanostructure; layered double hydroxides; memory effect; smart additives